Stakeholders’ views on barriers and facilitators of optimal support of individuals with Autism Spectrum Disorder in Macedonia - Vasilevska Petrovska, Ivana; Petrevska, Natalija; Trajkovski, Vladimir (Krakow Pedagogical University, 2021)
The aim of presented study was to explore barriers and facilitators of optimal support for social and developmental outcomes for people with ASD. The survey was based on the semistructured interviews with parents of people with ASD, as well as professionals supporting persons with ASD. Thematic analysis of the data was viewed with regard to positive and negative practices that essentially serve as barriers and facilitators of optimal support of individuals with ASD. The results showed three levels of perceived barriers and facilitators of optimal support: (1) individual – related to the level of autistic impairment, (2) attitudinal – related to social interpretation of individual behaviour and needs, and (3) systemic – related to the education and welfare approach and practice at macro level. Insights from viewpoints of key stakeholders represent indispensable considerations in promotion of health, equity and well-being of individuals with ASD and to inform the development of an individualized support system based on the person-centred planning approach.
Keywords: Autism Spectrum Disorder, barriers, facilitators, social participation, person- centred planning (PCP), Macedonia.